Relevansi Mekanisme Pasar Perspektif Abu Yusuf Pada Produk UMKM Bersertifikat Halal (Studi Kasus Majo Nugget Palembang) - Irina, Irina Kartika; Habsyah, Ade; Sumantri, Rinol; Iqbal, M.; Afif, Muhammad Faris (CV. Era Digital Nusantara, 2025)
One of the classical Islamic economic figures, Abu Yusuf, assumed that not always a small supply of goods causes expensive prices, likewise a large supply of goods causes prices to be cheap. Because in reality, prices do not depend on demand alone (supply) but also on the strength of supply (demand). According to Abu Yusuf, there are other variables that influence prices. This study aims to analyze the relevance of the increase in product prices at UMKM Majo Nugget using the concept of market mechanisms from Abu Yusuf's perspective. This research method is qualitative descriptive where data collection is done by means of an approach or interview with the research subjects and some data is taken from several other sources of articles, journals, and the internet. The results of the study show that demand and supply do not only depend on price but there is a supply side offered by UMKM Majo Nugget with its Halal MUI products so that consumers still want to buy these products. The relevance to Abu Yusuf's thinking is that the increase in the price of Majo Nugget products does not cause demand to fall, demand remains stable due to halal factors and product quality. This reflects the relevance of Abu Yusuf's theory in understanding current market dynamics.